How Pomerons meet in coloured glass - Ewerz, Carlo; Schatz, Volker (Nuclear physics. A, Nuclear and hadronic physics, 2004)
We compute the perturbative one-to-three Pomeron vertex in the colour glass condensate using the extended generalised leading logarithmic approximation in high energy QCD. The vertex is shown to be a conformal four-point function in two-dimensional impact parameter space. Our result can be used to compare different theoretical descriptions of the colour glass condensate.